2013
DOI: 10.1200/jco.2012.46.0147
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Instability Accounts for Reverse Metastatic Outcomes of Pediatric and Adult Synovial Sarcomas

Abstract: Metastasis development in SS is strongly associated with chromosome complexity, and CINSARC and Genomic Index are validated independent prognostic factors. The differences in metastasis frequency between adults and children are associated with genome instability, which is much more frequent in adults. Genomic Index is potentially the best overall biomarker and clearly the most clinically relevant, considering that genome profiling from formalin-fixed samples is already used in pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 32 publications
4
124
1
2
Order By: Relevance
“…Nevertheless, all parameters being equal, the outcome of adult patients with RMS is less favorable. Beyond the obvious difference in therapeutic approaches and management, the genomics of A‐RMS and E‐RMS should be compared between adult and children, similar to that performed for synovial sarcoma 42. Sharing the same classification would allow easier comparison between clinical presentation and behavior in adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, all parameters being equal, the outcome of adult patients with RMS is less favorable. Beyond the obvious difference in therapeutic approaches and management, the genomics of A‐RMS and E‐RMS should be compared between adult and children, similar to that performed for synovial sarcoma 42. Sharing the same classification would allow easier comparison between clinical presentation and behavior in adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…The same group assessed GI in SS and has shown that a high GI score of 2 predicts for a very poor metastasis-free survival in both pediatric and adult SS. 10 Indeed, the GI was higher in adults, indicating greater genomic instability, which offers a possible biological explanation for the poorer outcome in adults with SS. 7,11,13 Age as a prognostic factor has been clearly shown in several cancer registry series.…”
Section: Epidemiology Biology and Predictors Of Outcomementioning
confidence: 99%
“…9 However, the better outcome in younger patients in part is probably explained by SS biology, in particular, the role of the genomic index (GI). 10 Despite all the recent gains in knowledge, in particular, around biology, and a more defined role for chemotherapy, the outcome for SS has not significantly changed or, indeed, improved over recent years. Certainly, a recent report from the English national cancer registry on overall survival in the UK gives a 5-year relative survival of 57%, which compares with other population-based series and has not significantly changed over the past 20-year period in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to identify predictive biomarkers for response to TKI treatment in sarcoma, with a particular focus on synovial sarcoma, which is one of the most common soft tissue sarcomas in adolescents and young patients 14) . A magnetic bead-based assay was performed to identify predictive biomarkers in synovial sarcoma, and a meta-analysis was conducted to identify the gene expression pattern of the candidate biomarkers.…”
Section: Western Blottingmentioning
confidence: 99%
“…We used two microarray data sets as follows: 57 samples from GSE 54187 20) and 92 samples from GSE40025 14) . The microarray data were normalized and standardized using the Linear Models for Microarray Data (Limma) package (http:// bioconductor.org/packages/limma/) 21) .…”
Section: Meta-analysismentioning
confidence: 99%